A safe and simpler diagnosis of gastric schwannomas. Issue 4 (2nd February 2015) - Charepoo, Rambod; Palanisamy, Arun P.; Shetty, Jayakara; Kurtzman, Scott H.
Key Clinical Message Although gastric schwannomas usually are nonmalignant, these tumors can undergo malignant transformation. For diagnosis, endoluminal routes are believed to decrease the chance of cancerous cell dissemination. We present a case where a percutaneous route was utilized with supporting evidence for the safe use of this method for diagnosis.